Abilities of β-Estradiol to interact with chemotherapeutic drugs, signal transduction inhibitors and nutraceuticals and alter the proliferation of pancreatic cancer cells. (January 2020) - Akula, Shaw M.; Candido, Saverio; Abrams, Stephen L.; Steelman, Linda S.; Lertpiriyapong, Kvin; Cocco, Lucio; Ramazzotti, Giulia; Ratti, Stefano; Follo, Matilde Y.; Martelli, Alberto M.; Murata, Ramiro M.; Rosalen, Pedro L.; et al.
Abstract: Improving the effects of chemotherapy and reducing the side effects are important goals in cancer research. Various approaches have been examined to enhance the effectiveness of chemotherapy. For example, signal transduction inhibitors or hormonal based approaches have been included with chemo- or radio-therapy. MIA-PaCa-2 and BxPC-3 pancreatic ductal adenocarcinoma (PDAC) cells both express the estrogen receptor (ER). The effects of β-estradiol on the growth of PDAC cells has not been examined yet the ER is expressed in PDAC cells. We have examined the effects of combining β-estradiol with chemotherapeutic drugs, signal transcription inhibitors, natural products and nutraceuticals on PDAC. In most cases, inclusion of β-estradiol with chemotherapeutic drugs increased chemosensitivity. These results indicate some approaches involving β-estradiol which may be used to increase the effectiveness of chemotherapeutic and other drugs on the growth of PDAC.